2018
DOI: 10.1111/and.13009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of 49 infertile males with 45,X/46, XY mosaicism karyotype: A case series

Abstract: Disorders of sex development (DSD) are congenital abnormalities as an atypical development process in either gonadal or chromosomal structure. It is the cause of the abnormality in phenotype and characteristics. Chromosomal analysis plays an important role in the DSD determination. 45,X/46,XY mosaicism is a rare karyotype, and its prevalence is about 1.5 in 10,000 newborns. It affects the growth, hormonal balance, gonad development and histology. All data such as height, male general appearance, testis size an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Reviewing the literature, 45,X/46,XY mosaicism in males usually results either in azoospermia or severe reduced sperm production, elevated gonadotropins, and short stature [3, 4, 6, 9, 12]. Layman et al [3] presented three adult cases with 45,X/46,XY mosaicism in which one adult showed growth retardation as well as elevated gonadotropins and azoospermia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Reviewing the literature, 45,X/46,XY mosaicism in males usually results either in azoospermia or severe reduced sperm production, elevated gonadotropins, and short stature [3, 4, 6, 9, 12]. Layman et al [3] presented three adult cases with 45,X/46,XY mosaicism in which one adult showed growth retardation as well as elevated gonadotropins and azoospermia.…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral blood lymphocytes, the third case demonstrated 26% 45,X cells compared to the 6% 45,X cells in the present case. Interestingly, Mohammed Lashkari et al [6] reported 49 infertile males with 45,X/46,XY mosaicism in peripheral lymphocytes of whom, four cases were normozoospermic. Nonetheless, two of them presented with varicocele and the third had a high DFI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, four major X chromosome aberrations have been identified: (a) X chromosome numerical abnormality: for example, Klinefelter syndrome, 45, X/ 46, XY (Ropke & Tuttelmann, 2017). (b) X chromosome structural abnormality, involving X chromosome translocation, such as t (x; 18) (Q11; p11.1) and t (x; 14) (p11.4; P12) (Hwang et al, 2007; Mohammadpour Lashkari et al, 2018; Perrin et al, 2008); (c) CNV (Copy number variations) affecting X chromosome (Yatsenko et al, 2015); and (d) gene point mutation interfering with X chromosome, such as Rhox, tex11 and miRNA (Borgmann et al, 2016; Sha et al, 2018; Sosa, Flores, Yan, & McCarrey, 2015). X chromosome inversion is rare, and studies have shown that the phenotypic effect of X inversion is very heterogeneous (Madan, 1983).…”
Section: Introductionmentioning
confidence: 99%